Miss Julia rocks the cradle - Ross, Ann B. (Ross, Ann B. Miss Julia series., 2011)
Miss Julia's investigative work on a possible murder and her financial reputation keeps her buzzing. But the sudden arrival of Hazel Marie's twins during a fierce blizzard brings a whole new set of challenges and a double helping of trouble.